STRATEGI NAFKAH RUMAH TANGGA NELAYAN TRADISIONAL DI WILAYAH PESISIR PANTAI PAYUM KABUPATEN MERAUKE - Nurliah Nurliah; Ivonne Raystika Gretha Kaya (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
Payum is one of the coastal areas located not far from the center of Merauke city, where most of the people earn for living as traditional fishermen consisting of two groups of fishermen, namely local fishermen (Indigenous Papuans) and non-local fishermen (migrants) and have a dual livelihood strategy. This study aims to determine the livelihood strategy, the contribution of main and side income, and the composition of social strata based on income levels carried out by traditional fishing communities in the coastal area of Payum beach. The method is used was survey and qualitative approach (n=65 respondents) with sampling technique using Quota Sampling. The analysis method was carried out in 3 stages, namely: data reduction, data display, and conclusion drawing/verification. The results showed that the livelihood strategy involved family members, both wives and children with an income contribution of 80% from side income and 20% from main income. The main livelihood strategy is carried out by fishermen, while side income is carried out by other family members. The composition of social strata based on the income level of traditional fishermen of Payum beach is divided into 3 (three), are: (a) upper middle income; (b) lower middle income; and (c) lower income.